Refractory microsatellite stable metastatic colorectal cancer with ERBB2/ERBB3 mutation may be preferred population for regorafenib plus PD-1 inhibitor therapy: a real-world study - Dai, Xuan; Ding, Wenjun; He, Yongshan; Huang, Shiyong; Liu, Yun; Wu, Tingyu (Frontiers in Oncology, 2023)
Background: Microsatellite stable (MSS) colorectal cancer (CRC) has been referred to as the "cold tumor" due to almost no response to anti-PD1 antibody. A recent REGONIVO trial showed that regorafenib plus nivolumab had encouraging efficacy in MSS metastatic colorectal cancer (mCRC). However, only a small subset of patients may benefit from the combination therapy.We aim to evaluate the efficacy and safety data of immune checkpoint inhibitors combined with regorafenib in refractory MSS mCRC, and discover biomarkers that can effectively stratify the beneficial patient population. Methods: We retrospectively analyzed MSS mCRC patients who received regorafenib combined with anti-PD1 antibody therapy. Objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS) and status of gene mutation were reviewed and evaluated. Results: Twenty-one patients received combination treatment. At a median treatment duration of 4 months, 1 patient achieved CR, 3 patients achieved PR and 2 patients achieved SD as the best response. The ORR and DCR were 19% and 28.5% in the overall population. The median PFS was 4 months, and the median OS was 25 months. Only ERBB2/ERBB3 mutation status was confirmed to be a potential predictive factor for effective treatment. In patients with ERBB2/ERBB3 mutation, ORR, DCR and PFS exhibited significant improvements in comparison to wild-type patients. Grade 3 or higher treatment-related adverse events occurred in 3 patients (14.3%). Conclusions: Regorafenib in combination with PD1 inhibitor provide a feasible treatment regimen for refractory MSS mCRC with tolerated toxicity. Patients with ERBB2/ERBB3 mutation may be the preferred population for this combination regimen.